Prophylactic Role of Lactobacillus paracasei Exopolysaccharides on Colon Cancer Cells through Apoptosis Not Ferroptosis - Yalda Rahbar Saadat; Bahram Pourghassem Gargari; Arman Shahabi; Yousef Nami; Ahmad Yari Khosroushahi (Tabriz University of Medical Sciences, 2021)
Background: Nowadays despite conventional methods in colon cancer treatment, targeting vital molecular pathways and induction of various forms of cell death by safe probiotic components like exopolysaccharides (EPSs) are of great importance and are considered as potential therapeutic agents. This study aimed to investigate the inhibitory effect of the EPS of L. paracasei on different colon cancer cell lines (SW-480, HT-29, and HCT-116). Methods: For this purpose, several cellular and molecular experiments including MTS assay, DAPI staining, Annexin V/PI assay, quantitative real-time PCR (qPCR) and some important ferroptosis-related assays were performed. Results: Based on the findings, L. paracasei EPS can induce apoptosis confirmed by all apoptosis related assays and could not act through ferroptosis pathways. L. paracasei EPS could hinder the Akt1, mTOR, and Jak-1 mRNAs, and induces apoptosis through down-regulation of the antiapoptotic gene (Bcl-2), up-regulation of pro-apoptotic genes (BAX, caspase-3, 8). Conclusion: The exploited EPS of an indigenous probiotic strain with anticancer potential with low/insignificant cytotoxicity to normal cells is proposed for future applications in molecular targeted therapy of colon cancer treatment. Furthermore, in vivo and clinical trials should be performed to evaluate the applicability of this component besides conventional methods to increase the survival rate of colon cancer patients.